Personal Branding Pada Kalangan Mahasiswa FISIP Universitas Riau Kepulauan di Batam (Studi Pengguna iPhone) - Silalahi, Debora Martha; Indrawati, Indrawati (Peneliti.net, 2024)
This study aims For explain Personal Branding on circles student Faculty of Social And Political Riau Batam Island Universitry which uses second-hand iPhones. Background behind study This started from some students of FISIP UNRIKA who use second-hand iPhones from circles class medium as event For Personal Branding. Theory used For analyze study This that is theory interaction symbolic from George Herbert Mead. Study This use method ode study qualitative descriptive with technique snowball sampling, amount informant on study This as many as 6 people. Data collection was carried out with method interview deep And documentation , technique analysis use data reduction , data presentation , and data verification . The results study to show that Personal Branding of FISIP UNRIKA students with using a used iPhone can seen through 3 concepts in accordance with theory used that is interaction symbolic . Concept ; 1) Mind 2) Self 3) Society.